2018
DOI: 10.1093/jas/skx053
|View full text |Cite|
|
Sign up to set email alerts
|

Tiny but mighty: The role of the rumen microbes in livestock production

Abstract: The microbes inhabiting the rumen convert low-quality, fibrous, plant material into useable energy for the host ruminant. Consisting of bacteria, protozoa, fungi, archaea, and viruses, the rumen microbiome composes a sophisticated network of symbiosis essential to maintenance, immune function, and overall production efficiency of the host ruminant. Robert Hungate laid the foundation for rumen microbiome research. This area of research has expanded immensely with advances in methodology and technology that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 131 publications
0
17
0
3
Order By: Relevance
“…Calves fed FSBM13 had a greater proportion of Prevotella ruminicola in the rumen fluid. This proteolytic bacterium effectively consumes NH 3 -N, peptides and, to a lesser degree, uses AAs to produce microbial proteins and adenosine triphosphate (ATP) 51,52 . The PCA showed that Prevotella ruminicola was positively associated with the concentration of NH 3 -N in rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Calves fed FSBM13 had a greater proportion of Prevotella ruminicola in the rumen fluid. This proteolytic bacterium effectively consumes NH 3 -N, peptides and, to a lesser degree, uses AAs to produce microbial proteins and adenosine triphosphate (ATP) 51,52 . The PCA showed that Prevotella ruminicola was positively associated with the concentration of NH 3 -N in rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Domesticated ruminants such as cattle ( Bos taurus ), sheep ( Ovis aries ), goats ( Capra aegagrus ), and yaks ( Bos grunniens ) form an important segment of agriculture around the world with over 3.5 billion domesticated ruminants providing a source of high-quality animal protein in the form of meat and dairy products ( Cammack et al, 2018 ). Non-domesticated ruminants also fill essential ecological niches as primary consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In the rumen, protozoa, bacteria, and fungi communities ferment enzymatically structural carbohydrates, starch, and proteins. During the fermentation process, volatile fatty acids (VFA), CO 2 , and metabolic H 2 are produced and used by methanogenic archaea for the synthesis of CH 4 ( 7 ). Methanogenic archaea fluctuate between 10 7 and 10 9 cells per milliliter of rumen fluid ( 29 ) and approximately two thirds belong to the genus Methanobrevibacter and Methanosarcina ( 30 ) representing 1–4% of the microbial biomass.…”
Section: Methane Synthesismentioning
confidence: 99%
“…A fact which constrains anaerobic fermentation of organic matter and induces long retention times of digesta in the reticulo-rumen (4), leading to high emissions of enteric CH 4 (5). Under those circumstances, it has been claimed that secondary metabolites contained in a wide variety of plants may mitigate CH 4 emissions through a variety of mechanisms involving the rumen microbiome (6)(7)(8). Although secondary metabolites may be usually considered beneficial, the concentration of certain ergot alkaloids such as ergosine and ergocristine in pastures may lead to toxicity under certain circumstances in grazing animals such as sheep and horses (9).…”
Section: Introductionmentioning
confidence: 99%